Teaching spatial data science - Ane Rahbek Vierø; Michael Szell (Geoforum Perspektiv)
Spatial data science is an emerging field building on geographic information science, geography, and data science. Here we first discuss the definition and history of the field, arguing that it indeed warrants a new label. Then, we present the design of our course Geospatial Data Science at IT University of Copenhagen and discuss the importance of teaching not just spatial data science tools but also spatial and critical thinking. We conclude with a perspective on the potential future for spatial data science, arguing that qualitative theory and methods will continue to play an important role despite new GeoAI-related advances.